Myocardial Cell Preservation from Potential Cardiotoxic Drugs: The Role of Nanotechnologies - Adelaide Iervolino; Luigi Spadafora; Cristiano Spadaccio; Valentina Iervolino; Giuseppe Biondi Zoccai; Felicita Andreotti (MDPI AG, 2022)
Cardiotoxic therapies, whether chemotherapeutic or antibiotic, represent a burden for patients who may need to interrupt life-saving treatment because of serious complications. Cardiotoxicity is a broad term, spanning from forms of heart failure induction, particularly left ventricular systolic dysfunction, to induction of arrhythmias. Nanotechnologies emerged decades ago. They offer the possibility to modify the profiles of potentially toxic drugs and to abolish off-target side effects thanks to more favorable pharmacokinetics and dynamics. This relatively modern science encompasses nanocarriers (e.g., liposomes, niosomes, and dendrimers) and other delivery systems applicable to real-life clinical settings. We here review selected applications of nanotechnology to the fields of pharmacology and cardio-oncology. Heart tissue-sparing co-administration of nanocarriers bound to chemotherapeutics (such as anthracyclines and platinum agents) are discussed based on recent studies. Nanotechnology applications supporting the administration of potentially cardiotoxic oncological target therapies, antibiotics (especially macrolides and fluoroquinolones), or neuroactive agents are also summarized. The future of nanotechnologies includes studies to improve therapeutic safety and to encompass a broader range of pharmacological agents. The field merits investments and research, as testified by its exponential growth.